Weak Soft Separation Axioms and Weak Soft (1,2)*- -Separation Axioms in Soft Bitopological Spaces - Mahmood, Sabiha I (Al-Nahrain Journal of Science, 2018)
Abstract:In this article we introduce and study new types of soft sets in soft bitopological spaces, namely, soft (1,2)*-difference sets and soft (1,2)*-b-difference sets by using the notion of soft -open sets and soft (1,2)*-b-open sets respectively. Furthermore we use these soft sets to define and study new types of soft separation axioms, namely, soft (1,2)*- -spaces and soft (1,2)*-b- -spaces for which are weaker than soft (1,2)*- -spaces and soft (1,2)*-b- -spaces for respectively. The basic properties and characteristics each of soft (1,2)*-b- -spaces, soft (1,2)*- -spaces and soft (1,2)*-b- -spaces for also have been studied.